Tradução de termos simples, expressões fixas e semifixas em ciência política e economia política: um estudo baseado em corpus - Serpa, Talita [UNESP]; Camargo, Diva Cardoso de [UNESP] (My University, 2011)
This study discusses translations in English concerning the areas of Political Science and Political Economy, written by Fernando Henrique Cardoso & Enzo Falleto; and Antonio Carlos Bresser-Pereira. Our research project draws on CorpusBased Translation Studies (BAKER, 1993, 1995, 1996, 2000; CAMARGO, 2005, 2007), Corpus Linguistics (BERBER SARDINHA, 2004; TOGNINI-BONELLI, 2001) and on some concepts of Terminology (BARROS, 2004; KRIEGER & FINATTO, 2004). For compiling the comparable corpora in Portuguese and in English, we selected articles from Brazilian journals and from international journals of Political Science and Political Economy. We also present four samples of bilingual glossaries with the terms of these subareas in their cotexts.

Este estudo discute as traduções em língua inglesa de obras das subáreas de Ciência Política e Economia Política originalmente escritas em português pelos teóricos Fernando Henrique Cardoso & Enzo Falleto; e Antonio Carlos Bresser-Pereira. Para tanto, fundamentamo-nos nos Estudos da Tradução Baseados em Corpus (Baker, 1993, 1995, 1996, 2000; Camargo, 2005, 2007), na Linguística de Corpus (Berber Sardinha, 2004; Tognini-Bonelli, 2001) e, em parte, na Terminologia (Barros, 2004; Krieger & Finatto, 2004). Para compor os corpora comparáveis em português e em inglês, foram utilizados artigos de revistas brasileiras e revistas estrangeiras das subáreas referidas. Também apresentamos uma amostra de quatro glossários bilíngues com os termos destas subáreas em seus cotextos.
Translation of simple terms, semi-fixed and fixed expressions in political science and political economy: a study based on corpus
Keywords: Tradução especializada; Estudos de tradução baseados em corpus; Lingüística de Corpus; Economia Política; Corpus-Based Translation Studies; Corpus Linguistic; Political Science; Political Economy